Toxoplasma gondii causa alterações na túnica mucosa e no plexo submucoso do jejuno e do cólon proximal de ratos - Góis, Marcelo Biondaro (2015)
Intestinal inflammatory diseases are characterized by alterations that affect the intestinal mucosal cells, goblet cells, local immune system cells and enteric nervous system cells. The secretion of the intestinal epithelium is coordinated by the action of the submucosal plexus through chemical mediators, produced and released by enterocytes, lymphocytes and goblet cells that interact with neurons and enteric glial cells (EGCs), regulating the intestinal mucosa to amplify the immunobiological response, facilitate the intestinal transit and provide a direct action against infectious agents, among them Toxoplasma gondii, an etiological agent of toxoplasmosis, a worldwide-spread zoonosis. To investigate the effects of the chronic infection caused by T. gondii on the mucosal tunica, tela submucosa and submucosal plexus of the jejunum and proximal colon of rats. 20 Rattus norvegicus were utilized, and distributed into a control group (CG), which received one mL of sterile saline solution orally, and an infected group (IG), orally inoculated with a solution containing 500 oocysts of ME-49 strain of T. gondii in one mL of distilled water. Thirty-six days later, they were submitted to anesthetic procedure and euthanized. Samples of the jejunum and the proximal colon were harvested, fixed and submitted to histological processing to evaluate the submucosal tela and tunica using Hematoxilyn eosin, Periodic Acid Schiff and Alcian Blue staining techniques. Total preparations of the submucosal plexus were also done with Giemsa, histochemistry for NADH-diaphorase enzyme and immunohistochemistry to stain nervous and enteric glial cells, vasoactive intestinal polypeptide and S-100β pan glial proteins, respectively. Organs were harvested to perform bioassays in mice. The experimental protocol was efficient to induce infection in rats of IG in which anti-T. gondiiantibodies were detected in a serum exam and tissue cysts were isolated by bioassay. The following was observed in the jejunum: decrease of 12.3% of the tunica mucosa thickness, increase of 7.9% of the submucosal tela, 7.10% of villus height and 17.37% of crypt depths. The number of stained neurons by Giemsa and NADH-diaphorase decreased 15.38%and 40.71%, whereas the areas of the cell bodies increased 5.57 and 23.60%, respectively. There was a 19% reduction in the number of EGCs in the jejunum submucosal plexus. In the proximal colon, the tunica mucosa thickened 48.14% and the crypts deepened 43.02%. The total population of submucosal neurons stained by Giemsa decreased 16.20%. However, the neurons stained by immunohistochemistry for vasoactive intestinal polypeptide increased 25.95%. Intra-epithelial lymphocytes increased 62.86%. Goblet cells capable of producing sulfomucins were reduced by 22.87%. The chronic infection caused by T. gondii significantly altered the tunica mucosa, submucosal tela and induced the death of neurons in the submucosal plexus of the jejunum and proximal colon of rats.